Excess H+ Increases Hydrophilicity during CO2‑Assisted Enhanced Oil Recovery in Sandstone Reservoirs - Chen, Y.; Sari, A.; Xie, Q.; Saeedi, Ali (American Chemical Society, 2019)
CO 2 -assisted enhanced oil recovery appears to be a cost-effective and an environmentally friendly means to unlock remaining oil resources from sandstone reservoirs. While wettability alteration due to water uptake of CO 2 has been identified as one of the primary mechanisms to govern subsurface multiphase flow and thus residual oil saturations, few works have been done to explore the leading factor of wettability alteration and fewer works have looked beyond the quantitative characterization of this physical process. We hypothesized that water uptake of CO 2 provides excess H + which decreases electrostatic bridges of an oil-brine-sandstone system, thus increasing hydrophilicity. To test our hypothesis, we conducted three sets of contact angle measurements in non-carbonated and carbonated brines using muscovite substrates at the pressure of 3000 psi and temperature of 25 °C. Moreover, we performed a geochemical study to quantify how excess H + governs electrostatic bridges in the oil-brine-muscovite system bearing basal charged clays. Our contact angle measurements show that non-carbonated water gave a contact angle of 118°, whereas carbonated brine gave a contact angle of 30°, implying a strong hydrophilic system. Geochemical modeling demonstrates that excess H + substantially substitutes exchangeable cations (>Na) embedded in muscovite, thus decreasing electrostatic bridges between oil-brine-muscovite. This work provides a first quantitative investigation on how water uptake of CO 2 depresses the ion-exchange process between oil-brine-muscovite, thus leading to wettability alteration.